FACTORS AFFECTING THE TIME SPAN FOR SUBMITTING FINANCIAL REPORTS ON NON-CYCLICAL CONSUMER SECTOR COMPANIES - Prasdecia, Caroline Pieta Sekar; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this research is to analyze the effect of institutional ownership, independent board membership, company size, profitability, and leverage on the time span for submitting financial reports. The population of this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The sample of this research was 125 companies. Data processing using multiple linear regression analysis methods in this research using Eviews 13 software. The results of this research indicate that company size has a negative and significant effect on the time span for submitting financial reports. While institutional ownership, independent board membership, profitability, and leverage cannot prove the influence on the time span for submitting reports. Based on the results of this research, company investors can increase the size of the company in order to speed up the time for submitting financial reports and can convey company information to investors on time, so that investors can make economic decisions. So that companies need to strive to carry out their responsibilities and duties properly to report financial reports quickly and on time so that they can be useful for the company's future.